Preparation of chitosan-based nanofiber mats containing Soluplus® as a potential polymeric carrier by electrospinning process - Rizka Yulina; Irene Bonadies; Giovanni Dal Poggetto; Paola Laurienzo (Jurnal Litbang Industri, 2021)
A preparation of chitosan-based nanofiber mats loaded with Soluplus as a novel carrier polymer was carried out. Soluplus, a water-soluble amphiphilic copolymer, was added to provide a nanofiber structure that will be useful in applications as drug delivery system. In this study, a mixture of chitosan, polyethylene oxide (PEO), and Soluplus micelles was electrospun into nanofibers and characterized using SEM to observe the fiber morphology. Rhodamine (Rh) was used as a model molecule trapped inside Soluplus micelles. The results showed that chitosan-based nanofiber mats were successfully realized by electrospinning of the chitosan/PEO polymer blend solution at a ratio of 3:2 with 4 wt% total polymer concentration. The optimum electrospinning parameters to obtain the nanofibers were at 30 kV electrical potential, 0.2 ml/hour feed rate, and 30 cm distance between the needle tip and the collector. The addition of Soluplus at four times greater critical micelles concentration (CMC) was still able to provide smooth and bead-less nanofibers morphology. Nanofiber mats with Rh-Soluplus have an average fiber diameter of 56 nm, a slightly thinner than the nanofibers with chitosan/PEO alone (63 nm). A preliminary study of Rh release from Soluplus micelles, as well as from Soluplus loaded in the nanofiber mats, showed slower release of Rh from Soluplus loaded in the nanofiber mats compared to the free Soluplus.